The US President's Malaria Initiative, Plasmodium falciparum transmission and mortality: A modelling study. - Peter Winskill; Hannah C Slater; Jamie T Griffin; Azra C Ghani; Patrick G T Walker (PLoS Medicine)
Background Although significant progress has been made in reducing malaria transmission globally in recent years, a large number of people remain at risk and hence the gains made are fragile. Funding lags well behind amounts needed to protect all those at risk and ongoing contributions from major donors, such as the President's Malaria Initiative (PMI), are vital to maintain progress and pursue further reductions in burden. We use a mathematical modelling approach to estimate the impact of PMI investments to date in reducing malaria burden and to explore the potential negative impact on malaria burden should a proposed 44% reduction in PMI funding occur. Methods and findings We combined an established mathematical model of Plasmodium falciparum transmission dynamics with epidemiological, intervention, and PMI-financing data to estimate the contribution PMI has made to malaria control via funding for long-lasting insecticide treated nets (LLINs), indoor residual spraying (IRS), and artemisinin combination therapies (ACTs). We estimate that PMI has prevented 185 million (95% CrI: 138 million, 230 million) malaria cases and saved 940,049 (95% CrI: 545,228, 1.4 million) lives since 2005. If funding is maintained, PMI-funded interventions are estimated to avert a further 162 million (95% CrI: 116 million, 194 million) cases, saving a further 692,589 (95% CrI: 392,694, 955,653) lives between 2017 and 2020. With an estimate of US$94 (95% CrI: US$51, US$166) per Disability Adjusted Life Year (DALY) averted, PMI-funded interventions are highly cost-effective. We also demonstrate the further impact of this investment by reducing caseloads on health systems. If a 44% reduction in PMI funding were to occur, we predict that this loss of direct aid could result in an additional 67 million (95% CrI: 49 million, 82 million) cases and 290,649 (95% CrI: 167,208, 395,263) deaths between 2017 and 2020. We have not modelled indirect impacts of PMI funding (such as health systems strengthening) in this analysis. Conclusions Our model estimates that PMI has played a significant role in reducing malaria cases and deaths since its inception. Reductions in funding to PMI could lead to large increases in the number of malaria cases and deaths, damaging global goals of malaria control and elimination.